«NEW WORDS IN COLLOQUIAL SPEECH: THE ROLE OF SUFFIXES IN ENRICHING THE VOCABULARY OF THE RUSSIAN LANGUAGE» - Abdurakhmanova Kamila Dilshodovna (International Journal of Literature and Language Studies, 2026)
This paper examines the features of new word formation in modern colloquial speech through the use of suffixes. The study analyzes the reasons for the active development of this word-formation method, the influence of digital communication on linguistic processes, and the most common models of new word formation among young people. The research demonstrates that suffixation remains one of the most productive mechanisms for expanding the vocabulary of the Russian language.